1996
DOI: 10.1093/jxb/47.12.1927
|View full text |Cite
|
Sign up to set email alerts
|

RNase inLasallia hispanicaandCornicularia normoerica: multiplicity of electromorphs and activity changes during a hydration-dehydration cycle

Abstract: The presence of RNase activity has been detected in the two saxicolous lichen species, Lasallia hispanica (Frey) Sancho & Crespo and Cornicularia normoerica (Gunn.) DR. Activity was localized in the soluble fraction and had an acid optimum pH in both species. When proteins from the soluble fraction of the two lichens were separated by isoelectric focusing, multiple electromorphs with RNase activity were detected. L. hispanica RNase was separated into seven bands, characterized by pis 7, 6.28, 4.58, 4.45, 4.25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, the present study has not revealed a pattern of variation that could be related exclusively to the habitat or seasonal differences. RNase activity of these lichen species is dependent on the water status of the thalli, as has previously been shown (de los Rios et al 1996;de los Rios 1997). The microclimatic characterization of the habitats where the lichens were collected during the sampling period, has revealed frequent changes in relative humidity in the proximity of the thalli (de los Rios 1997).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, the present study has not revealed a pattern of variation that could be related exclusively to the habitat or seasonal differences. RNase activity of these lichen species is dependent on the water status of the thalli, as has previously been shown (de los Rios et al 1996;de los Rios 1997). The microclimatic characterization of the habitats where the lichens were collected during the sampling period, has revealed frequent changes in relative humidity in the proximity of the thalli (de los Rios 1997).…”
Section: Discussionsupporting
confidence: 65%
“…In the saxicolous lichens referred to above, L. hispanica, P. omphalodes and C. normoerica, the changing pattern of RNase activity in the course of a hydration-dehydration cycle has been studied. RNase activity increased markedly in three species when the thalli were maintained in a relative humidity of 100% and decreased again when the thalli were dehydrated, down to values similar to those of untreated thalli (de los Rios et al 1996). RNase activity in these lichens does not increase during desiccation, as has been shown in bryophytes and other organisms that can withstand dehydration (Bewley & Krochko 1982;Gniazdowska-Skocek & Bandurska 1994).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…One of the early activities of metabolism upon restoration of cell function after desiccation is thought to be transcript formation [ 1 ], in part because synthesis of antioxidant proteins protects cells from the rapid intracellular release of reactive oxygen species after rehydration [ 12 ]. However, RNA-degrading endonucleases released during rehydration [ 13 ], may reduce RNA quantity and quality [ 14 ]. After the effects of rehydration reach a steady-state condition representative of the natural lichen, further experimentation provides the opportunity to investigate a variety of questions such as the ecological plasticity of the lichen by monitoring phenotypic, physiological or transcriptional metrics in response to different rehydration conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in RNase activity are commonly observed in response to abiotic environmental stressors such as heat shock (Chang and Gallie 1997), salinity (Gomes Filho and Sodek 1988), hydration -dehydration (de los Rios et al 1996), O2-deprivation (Fennoy et al 1997). Also, ribonuclease activity is influenced by plant hormones such as abscisic acid (Panavas et al 1998), auxin (Vetter 1974), gibberellic acid (Brown and Ho 1986). In plants low temperature stress causes a number of physiological and developmental changes resulting from disturbances in fundamental cellular functions.…”
Section: Introductionmentioning
confidence: 99%